Quercetin-Coating Promotes Osteogenic Differentiation, Osseointegration and Anti-Inflammatory Properties of Nano-Topographic Modificated 3D-Printed Ti6Al4V Implant - Liu, Nian; Wang, Hui; Fu, Zeyu; Zhang, Chuxi; Hui, Wenyu; Wu, Jinyang; Zhang, Yong; Zhang, Shilei (Frontiers in Bioengineering and Biotechnology, 2022)
The capabilities of osseointegration and anti-inflammatory properties are of equal significance to the bio-inert titanium implant surface. Quercetin has proved its capacities of activating anti-inflammation through macrophage modulation and promoting osteogenic differentiation. Herein, we fabricated quercetin-coating on nano-topographic modificated 3D-printed Ti6Al4V implant surface. Subsequently the biological cells responses in vitro, anti-inflammatory and osseointegration performance in vivo were evaluated. In vitro studies indicated that quercetin-coating can enhance the adhesion and osteogenic differentiation of rBMSCs, while modulating the polarization of macrophages from M1 to M2 phase and improving the anti-inflammatory and vascular gene expression. Moreover, quercetin-loaded implants reduced the level of peri-implant inflammation and ameliorated new bone formation and rapid osseoinegration in vivo. Quercetin-coating might provide a feasible and favorable scheme for endowing 3D-printed titanium alloy implant surface with enhanced the rapid osseointegration and anti-inflammatory properties.